Pengaruh Model Explicit Instruction dalam Meningkatkan Keterampilan Vokasional Membuat Tempe bagi Anak Tunarungu - Seftia Sulfanita; Zulmiyetri Zulmiyetri (Universitas Negeri Padang, 2018)
The background of this study is the problem found in the Perwari Special School, Padang. The authe observed that there are five student whit hearing impairment in the class of Grade VII. The author observed that they look bored and were not eager to learn, and it was probably because the learning subjects tend to be monotonous or that they had already understood the subject. The objective of this study is to determine the effectiveness of Explicit Instruction Model to improve the vocational skills in making tempeh for students whit hearing impairment of Grade VII of Perwari Special School, Padang.The study employed an experimental method in the form of pre-experimental design whit one group pretest-posttest design type. The research object of the five students was treated whit pretest and then provided whit a treatment of explicit instruction model. They are then treated whit posttest to observer their ability after the treatment. The score of the pretest and posttest were processed through the use of the Mann Whitney test to examine the research hypotheses.